A Virtual Clinical Reasoning Case for Medical Students Using an Ophthalmology Model: A Case of Red Eye - Nisha Chadha; Douglas Fredrick; Alefiyah Malbari; Joanne Hojsak (Association of American Medical Colleges, 2021)
Introduction Triggered by the COVID-19 pandemic, medical education has moved online, tasking medical educators with developing virtual learning experiences. This is particularly challenging for less-represented disciplines, such as ophthalmology. We designed a red eye clinical reasoning case for preclinical medical students, which can be delivered virtually, using video conference software. Methods We developed a 90-minute red eye/clinical reasoning workshop for which prereading was assigned to students. We then delivered a virtual development session to nonophthalmologist copreceptors and provided a session faculty guide. The entire first-year medical student class (No. = 140) participated in one of four identical workshops, which included virtual small- and large-group discussions. Students completed a knowledge pre- and posttest, and an optional session postsurvey. Results Knowledge gains from pretest (No. = 94) to posttest (No. = 73) were statistically significant (p < .05), with average scores improving from 57% to 70%. Overall, students were satisfied, rating the following items 4 or 5 out of 5: session (86%, No. = 31), virtual format (83%, No. = 30), and if they recommended future use (69%, No. = 35). Discussion This novel, virtual clinical reasoning case simulated small- and large-group learning, achieved knowledge gains, and was well received by students. Minor technical challenges were encountered but successfully remedied, without apparent disruption to learning. This virtual medical education model can be used to enhance ophthalmology education in preclinical medical students and can be adapted for virtual design of other curricular content.